1990
DOI: 10.1111/j.0022-3646.1990.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF IRRADIANCE ON THE FATTY ACID COMPOSITION OF PHYTOPLANKTON1

Abstract: Eight species of marine phytoplankton commonly used in aquaculture were grown under a range of photon flux densities (PEDs) and analyzed for their fatty acid (FA) composition. Fatty and composition changed considerably at different PFDs although no consistent correlation between the relative proportion of a single FA and μ or chl a · cell−1 was apparent. Within an individual species the percentage of certain fatty acids covaried with PFDs, growth rate and/or chl a · cell−1. The light conditions which produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
123
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(143 citation statements)
references
References 31 publications
19
123
1
Order By: Relevance
“…For instance, nitrogen-limited conditions have repeatedly been shown to promote significant accumulation of neutral lipids for a wide collection of algal strains (Breuer et al, 2012;Griffiths et al, 2012;Erickson and Jimenez, 2013), and elevated PUFA levels have been reported at low light exposure (Thompson et al, 1990). This raises questions on the underlying cellular mechanisms, knowledge that could guide scientists to identify growth conditions and protocols that more efficiently target the intracellular pathways involved in lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, nitrogen-limited conditions have repeatedly been shown to promote significant accumulation of neutral lipids for a wide collection of algal strains (Breuer et al, 2012;Griffiths et al, 2012;Erickson and Jimenez, 2013), and elevated PUFA levels have been reported at low light exposure (Thompson et al, 1990). This raises questions on the underlying cellular mechanisms, knowledge that could guide scientists to identify growth conditions and protocols that more efficiently target the intracellular pathways involved in lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The intention with the group of algae grown under LL conditions was to include a study object with elevated PUFA levels. This was done partly based on the research by Thompson et al (1990), where most of the eight marine phytoplankton species investigated, including P. tricornutum, had their greatest proportion of EPA at low levels of irradiance. Despite previous findings, our GC-MS analyses could not discern any increase in EPA (all approximately 20 mg g 21 ) or in DHA (all approximately 1.5 mg g 21 ) at harvest of P. tricornutum grown under LL conditions compared with the Ctrl and NS categories (Table I).…”
Section: Fatty Acid Profiles As Determined By Gc-msmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these methods to estimate the relative importance of algal classes requires an estimate to be made of the ratios of pigments and fatty acids to a measure of biomass such as chlorophyll a (chl a). These may not necessarily be accurate, as the ratios of pigments and fatty acids can change, depending upon environmental conditions (Thompson et al 1990, Porra et al 1997). …”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The growth rates of dinoflagellates rarely double one per day (Thomas and Carr, 1985). Most of other economically important microalgae species have shown growth rates much higher than 1.0 d ) (Thompson et al, 1990). Different chemicals have been experimented for maximizing the biomass production and CO 2 bio-fixation of microalgae (Nayak et al, 2013).…”
Section: Discussionmentioning
confidence: 99%